KETIKA KEBIJAKAN ORDE LAMA MEMASUKI DOMAIN PENDIDIKAN: PENYIAPAN DAN KINERJA GURU SEKOLAH DASAR DI INDONESIA (Paramita: Historical Studies Journal, 2014)
This article reveals how the educational policy in Indonesia during The Old Order. The domination of government (Soekarno) as expressed in the domination theory by Antonio Gramsci which a politic is a commander and it can dominate whole Indonesia society life including an educational aspect. Furthermore, Soekarno as an individual manivesto has given a space for PKI because of their closeness. When the Minister, Prijono, issued a decision concerning about Pancawardhana Educational System, The Institution of National Education which is affiliated by PKI giving a formulation of Pancacinta. An education in the political manifesto obliges teachers enter into a practical politics life, teachers have to be revolutionary . It means that the learning practice is given toward students through indoctrination.  No less than 2000 teachers in the East java and the Cental Java finally became PKI members, then about  580 teachers of elementary school from the West Java. Even PKI has succeeded to divide the organization of teacher’s membership into The Cental Vak PGRI and  non Vak Central PGRI. Keywords : The Old Order, The Pacawardhana Educational System, the performance of elementary teachers.  Artikel ini mengungkapkan bagaimana kebijakan pendidikan Indonesia pada masa Orde Lama. Dominasi pemerintah (Soekarno) seperti diungkapkan dalam teori  dominasi oleh ntonio Gramsci di mana politik adalah panglima dan dapat mendominasi segala kehidupan masyarakat Indonesia termasuk dalam bidang pendidikan. Tidak hanya itu, Presiden Soekarno sebagai manivesto perseorangan  juga  telah  memberi ruang gerak pada PKI karena kedekatan hubungannya dengan Presiden Soekarno.  Ketika Menteri Prijono mengeluarkan keputusan tentang Sistem Pendidikan Pancawardhana, Lembaga Pendidikan Nasional yang berafiliasi dengan PKI memberi rumusan tentang Pancacinta. Pendidikan dalam alam manipol mengharuskan guru terjun dalam kehidupan politik praktis, guru harus revolusioner yang dalam praktik pembelajaran dilakukan kepada peserta didik melalui indoktrinasi.  Tidak kurang dari 2000 guru Jawa Timur dan Jawa Tengah akhirnya menjadi anggota PKI, demikian pula  kira-kira 580 orang guru sekolah dasar dari Jawa Barat.   Bahkan PKI telah berhasil memecah organisasi keanggotaan guru menjadi PGRI Vak Sentral dan PGRI non Vak Sentral. Kata Kunci : Orde Lama, Sistem Pendidikan Pancawardhana, Kinerja Guru SD.